The effect of differing kidney disease treatment modalities and organ donation and transplantation practices on health expenditure and patient outcomes. Issue 4 (2nd July 2017) - Jager, Kitty J; Stel, Vianda S; Branger, Peter; Guijt, Marja; Busic, Mirela; Dragović, Marijana; Diekmann, Fritz; Manyalich, Martí; Di Ciaccio, Paola; Nanni Costa, Alessandro; Collett, Dave; Mumford, Lisa; et al.
Abstract: The Effect of Differing Kidney Disease Treatment Modalities and Organ Donation and Transplantation Practices on Health Expenditure and Patient Outcomes (EDITH) aims to obtain information on long-term kidney transplant outcomes, long-term health outcomes of living kidney donors and detailed outcomes and costs related to the different treatment modalities of end-stage kidney disease. Nine partners from seven European Union countries will participate in this project.